Charakterystyka lasu grądowego z jodłą w rezerwacie „Jamno” - Woziwoda, Beata; Pawicka, Katarzyna; Wolski, Grzegorz J. (Biuletyn Szadkowski, 2012)
The “Jamno” nature reserve was established to protect the forest community with European silver fir Abies alba Mill. on the northern border of natural occurrence of this tree species in Poland. The results of current phytosociological studies (done in 2011) show that the oak-hornbeam forest – “Tilio-Carpinetum calamagrostietosum” association with “Abies alba”, exist within reserve. The present structure and species composition of studied community is determined by spontaneous changes of tree stand. The different proportion of silver fir in shrub and tree stand layers indicate the dynamic changes within this species population.